Flexor Pollicis Longus Tendon Rupture and Carpal Tunnel Syndrome due to Scaphoid Nonunion Advanced Collapse: A Case Report. Issue 3 (22nd July 2022) - Ikumi, Akira; Ichimura, Harumitsu; Asanuma, Sho; Nagashima, Katsuya; Takeuchi, Yousuke; Tatsumura, Masaki; Mammoto, Takeo; Ogawa, Takeshi; Yoshii, Yuichi; Hirano, Atsushi; Yamazaki, Masashi
Abstract : Case: We report a case of flexor pollicis longus (FPL) tendon rupture and carpal tunnel syndrome due to scaphoid nonunion advanced collapse deformity. Intraoperative findings showed disruption of the palmar joint capsule and a sharp proximal bone fragment protruding into the carpal tunnel. Removal of this proximal fragment and tendon grafting were performed. At the postoperative 2-year follow-up, the patient had no wrist pain, finger numbness, or restriction of thumb motion. Conclusion: Our results suggest that minimally invasive surgical procedures, such as proximal pole or osteophyte resection, might be optimal choices for early rehabilitation after tendon repair in cases of FPL tendon rupture due to asymptomatic scaphoid nonunion.